Compostos bioativos e atividade antioxidante de pétalas de rosas de corte - Prata, Gabriele Gruska Benevides (2009)
The objective of this study was to evaluate the presence of bioactive compounds and the antioxidant capacity of cut roses, aiming to evaluate the potential for being used as food. For this purpose, it was used thirteen genotypes of fresh roses petals subjected to analysis of coloration, pH, titratable acidity, soluble solids, soluble solids/ titratable acidity, total soluble sugars, reducing sugars, ascorbic acid, total pectin soluble pectin, bioactive compounds (flavonoids yellow, anthocyanins, carotenoids, total extractable polyphenols), total antioxidant activity (ABTS method) , chlorophyll, minerals (phosphorus, potassium, sodium, calcium, magnesium, copper, iron, manganese, zinc and sulfur), chemical composition (lipids, proteins, carbohydrates, fiber, ash, moisture). The results showed that the roses are low-acid vegetables, with a moderate level of soluble sugars (2,89g.100g-1) and reducing sugars (2,75g.100g-1), low levels of total and soluble pectin (0,07mg.100g-1 and 0,04mg.100g-1), good amount of ascorbic acid (70,47mg.100g-1), flavonoids yellow and anthocyanins reached values of 140,60mg.100g-1 and 356,77mg.100g-1, respectively. They have low levels of carotenoids, obtaining average 1.25mg.100g-1, high content of total extractable polyphenols (2550,03mg.100g-1), high antioxidant capacity (222,27μM trolox-1). The evaluation of the mineral contents reported that roses presents low contents of phosphorus (1,31mg.100g-1), potassium (18,77mg.100g-1), sodium (0,29mg.100g-1), calcium (2,07mg.100g-1), magnesium (2,12mg.100g-1) and sulfur (2,67mg.100g-1) and values that have considered copper (9,27mg.100g-1), iron (85,76mg.100g-1), manganese (22,06mg.100g-1) and zinc (35,20mg.100g-1). The descriptive statistics of the results was obtained by the use of software M-statc and Genes. Values quantified in this study were within the variations found in other plant foods commonly consumed. Thus, the roses have potential to be used for human feeding.